Yield evaluation of maize varieties grown for grain in the organic and integrated system - Księżak, Jerzy (Polish Journal of Agronomy, 2021)
The research aimed to determine the yield level of selected maize varieties grown for grain with organic and inte-grated farming systems. The field experiment was conducted in 2017–2019 at Kępa Agricultural Experimental Station using the method of crossed sub-block method in 4 replications. The first-order factor was the maize variety, the second-order factor – the production system. The assessed maize varieties cultivated in the integrated system (after wheat and stubble intercrop in combi-nation with natural and mineral fertilization) yielded better, on average by 12.1% than in the organic system. Maize grown in the integrated system was characterized by a 4.1% greater weight of a thousand grains, a 3.6% greater weight of grain from one cob, and a 2% greater number of grains per cob than in the organic system. The maize plants were about 6.5% higher and set the cob about 10% higher than in the organic system. However, the length and diameter of the cob as well as the proportion of grain in the cob were similar in both production systems. In the organic system, the cultivation of the cultivars Ambrosini and Silvestre ensured a yield level higher by about 8% (on average 9.4 t ha-1) compared to the average yields of the cultivars Smolitop and Ricardinio. In the integrated system, Ambrosini and Ricardinio yielded better (on average 10 t ha-1), the grain yield was 9.2% higher than the other two cultivars. In both production systems, Smolitop had the lowest yield; its yield was around 10% lower than that of Ambro-sini in the organic system and that of Ricardinio in the integrated system. The highest weight and number of grains per cob, irre-spectively of the production system, was characterized by Ricar-dinio, and the lowest by Smolitop (the difference was 5.1% and 9.4%, respectively). Ambrosini was characterized by the smallest caryopsis (307 g on average), while Smolitop was larger by about 21 g. Plants of Ricardinio were the tallest and set the cob highest on the stem regardless of the production system. However, the length and diameter of the cob of the tested cultivars were similar.